Pendampingan Pengolahan Koleksi Buku Pada Taman Bacaan Masyarakat PKBM Yabes Medan - Miftha Khulzannah (Fakultas Ushuluddin, Adab, dan Dakwah, 2023)
Processing of library materials is important to do to facilitate information retrieval and expedite service activities. Processing of library materials is work or activities that must be carried out in a library, namely from the time library materials are received at the library until they are ready to be used by users. Library material processing activities are the process of completing library materials that have been obtained so that they can easily be arranged in places or on shelves that have been provided to be sent to users. The purpose of this activity is to increase the knowledge of TBM PKBM Yabes Medan managers in processing book collections, to make it easier for users to manage existing collections so that they are ready-to-use and optimally usable so that all collections can be found, traced and used easily by users, because Processing is a job. sequential, mechanical and systematic. The result of this activity is that the implementation of community service runs smoothly according to the expectations of the community service implementing team, the participants feel that this community service activity is useful, because the participants are aware of the importance of processing book collections in preserving library materials owned by the library, the participants' responses for the service activities carried out stated that the delivery of the material was good and the participants understood the explanation given. This is shown by the interactive atmosphere between the participants and the service team. As well as with assistance in processing book collections, it will add insight both theoretically and practically regarding procedures for processing book collections that are good and correct.